(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Strategies for adapting to climate change include making allowances for the changed weatherpatterns. The purpose of this research is to evaluate how climate change affects environmentalsustainability. Industrial pollution, soil degradation, and natural catastrophes brought on by globalwarming all pose serious threats to sustainability in many parts of the globe. As this researchdemonstrates, natural resource management and adaptation techniques are not mutually exclusiverather, they are complementary. As a result, they may improve the effectiveness and adaptability ofexisting resources in the face of climate change. Weather patterns from the tropics to the poles areseeing long-term shifts due to climate change. As a worldwide danger, it has already begun exertingpressure on many different industries. The purpose of this research is to conceptually engineer howchanges in climate are threatening the viability of several industries throughout the globe. Certain food,water, and vector-borne illnesses are more likely to spread during times of extreme weather, as wasrecently shown with the coronavirus epidemic.